The Implication Of The Central Honorary Council’s Regulation In Limiting The Number Of Notarial Deeds - Nurul Inayah Eka Putri; Marwati Riza; Kahar Lahae (International Journal of Education, Vocational and Social Science, 2023)
The purposes of this study are: 1. To analyze the effectiveness of the supervisory role of the Notary Supervisory Board based on Central Honorary Council regulation Number 1 of 2017 concerning the Limit of the Reasonable Number of Deeds Per Day (Per.DKP No.1/2017). In addition, the purpose of this study is also to analyze the legal implications for notarial deeds made exceeding the fairness limit as stipulated in Central Honorary Council Regulation Number 1 of 2017 (Per. DKP No.1/2017). Research method. The approach taken by researchers is to use empirical methods. This research was carried out in several cities/regencies in South Sulawesi, namely the Regional Supervisory Board and Regional Supervisory Board of South Sulawesi Province and several Notary Offices whose locations are still under the authority of the Regional Supervisory Council. Furthermore, the samples were taken using the Simple Random Sampling method. The types and sources of data needed in this study were divided into two types of data: primary data, secondary data, and tertiary data. Data collection techniques were library research and field research. Data analysis, namely primary data and secondary data in this study were analyzed qualitatively, namely describing and systematically compiling the data obtained from the interview results, to achieve clarity of the issues discussed. Research result : 1) Based on its position, the Central Ethics Council Regulation Number 1 of 2017 comes with the hope that it can be a complement to the Notary Office Law, even though the limit on the number of making deeds per day is not explicitly stated in it, Article 2 of the Central Honors Council Regulation Number 1 of 2017 indirectly still has a thread related to the enforcement of the Notary Office Law, and 2) With regard to the sanctions given to notaries whose deed exceeds the fairness limit, in fact on the ground the Regional Supervisory Council stated that in fact on the ground they had not received information either within the South Sulawesi region or outside South Sulawesi regarding the imposition of sanctions by the Supervisory Council for making more than 20 deed per day.